The Effect of ICT Literation in Government Financial Management in Industry 4.0 Era - Yaumil Akhir , Garda; Murwaningsari, Etty (KnE Social Sciences, 2020)
In this Industry 4.0 era, ICT things grows so rapidly. The use of technology in daily work is a common thing. Thus, no exception, in the field of government. This extensive utilization of ICT then requires every civil servant to have sufficient knowledge in ICT. This study aimed to determine the effect of ICT Literation in moderating treasurer’s competence and implementation of acrual based accounting system for determining the quality of financial report in Ministry of Finance. The method used in this study is literature study method, documents study, and questionnaire. We found that in general, ICT Literation is moderating the relationship between treasurer’s, implementation of acrual based accounting system and financial report’s quality. Furthermore, in partial analysis, we found that ICT Literation affect treasurer’s competence in postive and significant ways, but for implementation of acrual based accounting system the effect is not significant. Keywords: Acrual Based Accounting System, Financial Report’s Quality, Human Resource’s Competence, ICT Literation.